Pilihan Rasional Perempuan Madura Dalam Pemertahanan Tradisi Minum Jamu Di Kabupaten Bangkalan Dan Sumenep - Ekna Satriyati; Alfan Biroli; Siti Nur Hana (JSPH (Jurnal Sosiologi Pendidikan Humanis), 2019)
The number of women in Indonesia who are aware of the importance of maintaining medical health is increasing along with the improvement of medical health services and facilities provided by the Government of the Republic of Indonesia. However, the number of women in various parts of Indonesia who still trust traditional health services and facilities is also not small. One of them is Madura Woman who believes in the tradition of drinking herbal medicine. The tradition is as a means of maintaining health and treating illness that is trusted between generations. Various studies show that the decision to maintain the tradition of drinking herbal medicine is based on trust and economic price. The rational choice of women towards health and treatment is often synonymous with easy, cheap and fast. However, in this article the discussion of the rational choice of Madurese women maintains the tradition of drinking herbal medicine by using cost, reward and alternative comparison. The results of the analysis of the decision of Madurese women who still maintain the tradition of drinking herbal medicine is a form of rational choice in maintaining health and treating illness. The study method uses qualitative by means of observation and interviews with selected informants namely two women in Bangkalan District and two women in Sumenep Regency.